Testing of rotating Einstein-Yang-Mills-Higgs black hole through QPOs - Ashraf, Asifa; Javed, Faisal; Maurya, S. K.; Channuie, Phongpichit; Cilli, Arzu; Gudekli, Ertan (ELSEVIER, 2025)
We investigate the influence of model parameters on the orbital and epicyclic motion of test particles around a spinning Einstein-Yang-Mills-Higgs black hole. A black hole having four defining parameters is its mass M, its rotation parameter a, a constant, beta and the theory parameter B. Formulas for the specific energy and angular momentum of the circular orbits in an equatorial plane are derived analytically. The stability of the spherical equatorial orbit is also examined using the effective potential method. We obtain analytical formulas for the particle frequencies of the radial, vertical, and orbital oscillations in relation to the properties of the black hole model under consideration. The main characteristics of quasi-periodic oscillations close to the stable circular orbits are discussed. Furthermore, we examine the precessions of Periastron and Lense-Thirring. It is concluded that the parameters of the consider black hole model strongly influence the motion of the particles around the black hole.
Keywords: Black hole; Particle dynamics; Epicyclic motion; QUASI-PERIODIC OSCILLATIONS; THIN ACCRETION DISKS; PARTICLE MOTION; BARYON NUMBER; MASS; NONEXISTENCE; UNIQUENESS; Astronomy & Astrophysics